MUSIC IN KOJIKI - Wesołowska, Marta (Porównania, 2017)
This article focuses on the descriptions of music in Kojiki (Record of Ancient Matters, 712) − the oldest existing chronicle of Japan. The author discusses respectively: the circumstances of the creation of Kojiki (activity of Hieda no Are, the compiler from Gagakuryō Japanese Court Music Bureau), the characteristics of early Japanese performing art traditions (kagura ritual dance, chinkon ceremony of recalling the soul), the analysis of ancient folk songs kayō and the symbolism of the oldest musical instruments. The analysis of the selected musical descriptions was carried out in regard to the socio-cultural context as well as the linguistic aspects. Based on the evidence material presented in this article, the author characterized the musical life of ancient Japan. Special attention was also paid to the role of music in shaping the literary work.